Makna Teologis Frasa “Waktunya Sudah Dekat” Dalam Wahyu 22:10 Dan Implikasinya - Wesley, Jhon; Yakob, Yakob (STTI Harvest Semarang, 2023)
The phrase “the time is near” is one of the passages that has become familiar among Christians in understanding the second coming of Christ to earth. However, there are many Christians who do not understand the theological meaning of this word precisely. No wonder the coming of Christ becomes meaningless for some believers. Some think it's just a fictional story. However, some people try to interpret the coming of the Lord Jesus with calendar dates. Actually, what is the theological meaning and urgency of the phrase above? This article aims to discuss the meaning of the phrase